Hearing changes after temporomandibular joint arthroscopy:a prospective study - Ângelo, D.F. (2021)
Temporomandibular Joint (TMJ) arthroscopy is considered an effective and safe minimally invasive surgical approach. While the long-term outcomes of arthroscopy tend to be positive and free of secondary effects, patients occasionally complain about their hearing following the treatment. The aim of this prospective study was to investigate possible hearing changes associated with TMJ arthroscopy. Pure-tone audiograms were performed in patients two weeks before TMJ arthroscopy and repeated six weeks after intervention. A total of 15 patients (mean age of 41.73±16.36) were enrolled; 25 TMJ arthroscopies were performed (five unilateral and ten bilateral). Statistically significant differences were found between preoperative and postoperative audiograms in the frequencies 256Hz (P=0.011) and 8kHz (P=0.058, borderline). For the frequency 256Hz the difference was favourable, but not superior to 5dB. For the frequency 8kHz, in three patients the TMJ arthroscopy resulted in a decrease of 10dB. However, no clinical hearing changes or complaints were observed in the involved patients. No differences in audiograms between level 1 or 2 arthroscopy were observed. The study reinforces the safety of the TMJ arthroscopy level 1 and 2 with the reported protocol. The authors recommend larger studies to validate the results, specially for frequency 8kHz.